ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI PADA BANK UMUM SYARIAH DI INDONESIA - Devi Supriatin1,Suryana2, Suci Aprilliani Utami3 (UIN Mataram, 2019)
This study aims to determine the level of efficiency of Islamic Commercial Banks (BUS) in Indonesia, as well as to analyze the factors that influence the level of efficiency. Variables used in measuring bank efficiency include input variables consisting of total assets and total Third Party Funds (DPK) while output variables consist of total financing. Furthermore, this study examines the effect of the independent variables in the form of Return On Assets (ROA), BOPO, and Non Performing Financing (NPF) on the dependent variable, namely the value of efficiency. The analysis method used is the Stochastic Frontier Analysis (SFA) analysis and panel data regression. The results of this study indicate that: 1. The results of the calculation of efficiency using the Stochastic Frontier Analysis (SFA) method show the high level of efficiency of Islamic Commercial Banks (BUS), which is almost close to 100%, which means it is almost efficient. 2. Reutrn On Assets (ROA) significantly influence the Performance Efficiency of Islamic Commercial Banks 3. BOPO significantly influences the Efficiency Performance of Islamic Commercial Banks. 4. Net Performing Financing (NPF) does not significantly influence the Performance Efficiency of Islamic Commercial Banks.